Hepatocyte-Specific Knock-Out of Nfib Aggravates Hepatocellular Tumorigenesis via Enhancing Urea Cycle - Zhou, Li; Wang, Qing-Liang; Mao, Lin-Hong; Chen, Si-Yuan; Yang, Zi-Han; Liu, Xue; Gao, Yu-Hua; Li, Xiao-Qin; Zhou, Zhi-Hang; He, Song (Frontiers in Molecular Biosciences, 2022)
Nuclear Factor I B (NFIB) has been reported to promote tumor growth, metastasis, and liver regeneration, but its mechanism in liver cancer is not fully elucidated. The present study aims to reveal the role of NFIB in hepatocellular carcinogenesis. In our study, we constructed hepatocyte-specific NFIB gene knockout mice with CRISPR/Cas9 technology (Nfib-/-; Alb-cre), and induced liver cancer mouse model by intraperitoneal injection of DEN/CCl4. First, we found that Nfib-/-; Alb-cre mice developed more tumor nodules and had heavier livers than wild-type mice. H&E staining indicated that the liver histological severity of Nfib-/- group was more serious than that of WT group. Then we found that the differentially expressed genes in the tumor tissue between Nfib-/- mice and wild type mice were enriched in urea cycle. Furthermore, ASS1 and CPS1, the core enzymes of the urea cycle, were significantly upregulated in Nfib-/- tumors. Subsequently, we validated that the expression of ASS1 and CPS1 increased after knockdown of NFIB by lentivirus in normal hepatocytes and also promoted cell proliferation in vitro. In addition, ChIP assay confirmed that NFIB can bind with promoter region of both ASS1 and CPS1 gene. Our study reveals for the first time that hepatocyte-specific knock-out of Nfib aggravates hepatocellular tumor development by enhancing the urea cycle.